The attentional boost effect with semantic information detection tasks. Issue 3 (March 2021) - Zheng, Siqi; Meng, Yingfang; Lin, Guyang
The attentional boost effect (ABE) is a phenomenon in which in some dual tasks, increased attention to target detection causes an increase in memory performance related to items paired with the target. However, in previous studies concerning the ABE, the detection task objects usually reflected perceptual information. Whether the ABE could be observed if the task involves detecting semantic information is unclear. To answer this question, the present study adopted the classic dual-task paradigm of the ABE. Arabic numerals were used as semantic information stimuli in the detection tasks, and the degree of semantic processing in the detection task gradually increased over three experiments. The results showed that target detection with semantic information (i.e., digits) triggered the ABE (Experiment 1) and that the ABE was also generated under the semantic judgement-based detection task (i.e., odd–even detection task) regardless of whether the detection task used a single-target stimulus (Experiment 2) or a multi-target stimulus (Experiment 3). These findings indicate that an increased semantic load before the target decision in the detection task does not affect the ABE, and both perceptual detection and semantic detection can trigger the ABE.